The Recommendation To Hold A Walimah In The View Of The People Of Banjarmasin City - Ridwan, Muhammad; Ainah, Nur (Sharia Journal and Education Center Publishing, 2024)
Abstract This research examines the views or understanding of the people of Banjarmasin City regarding the implementation of marriage guardians regarding the hadith of the Prophet Muhammad SAW. However, the aim of the research is to find out the actual law for implementing a marriage walimah because the Prophet's Hadith states that it is highly recommended that the walimah be hastened. The main problem in this case is how the public truly understands the hadith of the Prophet which contains recommendations for implementing walimatul 'ursy, whether this walimatul 'ursy must be implemented or is it just a recommendation. In this matter, there are differences of opinion from several sects of imams. In Islamic jurisprudence, walimah can be interpreted specifically and generally. The general meaning of walimah is a celebration event that involves many people. Meanwhile, the specific meaning of walimah or what can be called walimatul 'ursy is the inauguration of a wedding with the aim of informing the public that the bride and groom are legally or officially husband and wife. Keywords: Walimah, Recommended, Community, Banjarmasin Abstrak Penelitian ini mengkaji mengenai pandangan atau pemahaman masyarakat Kota Banjarmasin terhadap pelakasanaan walimah pernikahan terhadap hadist Nabi Muhammad SAW. Namun, tujuan penelitian adalah untuk mengetahui hukum sebenarnya pelaksaan walimah pernikahan karena pada Hadist Nabi tersebut menyatakan bahwa walimah sangatlah dianjurkan untuk disegerakan. Masalah utama dalam hal ini adalah bagaimana cara masyarakat memahami sebenar-benarnya tentang hadist Nabi yang berisi anjuran untuk melaksanakan walimatul ‘ursy, apakah walimatul ‘ursy ini wajib dilaksanakan atau hanya sekedar anjuran. Dalam hal ini, terdapat perbedaan pendapat dari beberapa imam mazhab. Di dalam fiqih Islam, walimah bisa dimaknai khusus dan umum. Makna umum walimah yaitu acara perayaan yang melibatkan banyak orang. Sedangkan makna walimah secara khusus atau bisa di sebut walimatul ‘ursy adalah peresmian pernikahan dengan tujuan memberitahukan kepada masyarakat bahwa kedua mempelai telah sah atau resmi menjadi suami istri. Kata Kunci: Walimah, Anjuran, Masyarakat, Banjarmasin